Internship at the User-Oriented Grand Library - Merve Çetinkaya; B. Yağmur Kurşun (Türk Kütüphaneciliği)
Students from the Department of Information and Records Management, Faculty of Humanities, Ankara University share their impressions of the internship experience they gained at the Grand Library of Near East University in Turkish Republic of Northern Cyprus.